Penerapan Model Pembelajaran Problem Solving untuk Meningkatkan Hasil Belajar Kimia Siswa Kelas XI SMA - Hasniwati Lubis (Jurnal Inovasi Pembelajaran Kimia (Journal Of Innovation in Chemistry Education), 2021)
This study aimed to determine the increase in student learning outcomes in the domain of knowledge, skills, and attitudes by using problem-solving learning models. The method used is classroom action research through two learning cycles consisting of the stages of planning, implementing, observing, and reflecting. There was an increase in learning outcomes and the number of students who met the minimum completeness in the domain of knowledge seen from the average value of students in cycle 1 to cycle 2. The learning outcomes of students in the domain of skills from the observation were included in the sufficient criteria in cycle 1 and increased to be good criteria in cycle 2. Classical completeness based on the number of students in cycle 1 to cycle 2 has increased. The learning outcomes of students in the domain of attitudes through the results of observation data were included in the sufficient criteria in cycle 1 and increased to be good criteria in cycle 2. As well as an increase in completeness seen from the number of students in cycle I to cycle II. Based on these findings, this model can be used to improve the chemistry learning outcomes of students in class XI.